(untitled) (Asian Journal of Current Engineering and Maths, 2013)
In this workÂ Â Homotopy Perturbation transform Method (HPTM) is used for analytical treatment of the Cauchy Reaction-Diffusion equations .This method is the combined form of Homotopy perturbation method and Laplace transform method. The Nonlinear terms can be easily decomposed by use of Heâ€™s polynomials. This method can provide analytical solutions to the problems by just utilizing the initial conditions. The proposed iterative scheme finds the solution without any discretization, linearization or restrictive assumptions. The proposed method solves nonlinear problems without using Adomain polynomials which is the advantage of this method over Adomain Decomposition method. The results reveal that the HPTM is very effective, simple, convenient, flexible and accurate. Outcomes prove that HPTM is in very good agreement with ADM, VIM and HPM.